Jasper Jumper - Nazan Küçükkeleş; Ata Orgun (Galenos Yayinevi, 1993)
Functional approach to Class II div. I cases is a commonly used method, Jasper Jumper which was described in this paper is an alternative to the other functional appliances as being a fixed one. In this pilot study which contains 5 cases we aimed to describe the mechanic and observe the treatment effects on skeletal and dental structures.